2020
DOI: 10.4049/jimmunol.1900094
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Regulation of the Mucosal Mast Cell–Specific Protease Genes Mcpt1 and Mcpt2 by GATA and Smad Transcription Factors

Abstract: Mouse mast cell proteases (mMCP)-1 and -2 are specifically expressed in mucosal mast cells (MCs). However, the transcriptional regulation mechanism of the Mcpt1 and Mcpt2 genes induced in mucosal MCs is largely unknown. In the current study, we found that TGF-b stimulation drastically induced upregulation of Mcpt1 and Mcpt2 mRNA in mouse bone marrow-derived MCs (BMMCs). TGF-b-induced expression of Mcpt1 and Mcpt2 was markedly suppressed by transfection with small interfering RNA targeting Smad2 or Smad4 and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The stimulatory response displayed by MCs in these circumstances could be the result of an evolutionary advantage to resist immunosuppression by parasites/worms; MCs may also activate to some degree in the context of wound repair. TGF-β1 stimulation of murine bone marrow-derived MCs is also sufficient in inducing mMCP-1 and mMCP-2 expression facilitated through GATA2 and Smad (2,4, potentially 3) signaling [82]. This response may prime MCs as localized protective effector cells during wound repair or during the resolution of an immune response in tissues.…”
Section: Il-10 and Tgf-β1mentioning
confidence: 99%
“…The stimulatory response displayed by MCs in these circumstances could be the result of an evolutionary advantage to resist immunosuppression by parasites/worms; MCs may also activate to some degree in the context of wound repair. TGF-β1 stimulation of murine bone marrow-derived MCs is also sufficient in inducing mMCP-1 and mMCP-2 expression facilitated through GATA2 and Smad (2,4, potentially 3) signaling [82]. This response may prime MCs as localized protective effector cells during wound repair or during the resolution of an immune response in tissues.…”
Section: Il-10 and Tgf-β1mentioning
confidence: 99%
“…Accumulating evidence showed that transcription factors can play a critical role in proliferation, differentiation, and activation of MCs. 32,33 Some transcription factors such as Crem, fosB, and Nr4a3 are known to be involved in FcεR-mediated immune responses of MCs. 34,35 Therefore, association with MC activation and Nr4a3 is implicated in various physiological and pathophysiological processes including, immune and inflammatory responses, apoptosis, and cell cycle control.…”
Section: Discussionmentioning
confidence: 99%
“…Among identified candidate genes, transcription factor genes showed the greatest upregulation (e.g., Scrt1, 15.94 fold; Nr4a3, 8.44 fold). Accumulating evidence showed that transcription factors can play a critical role in proliferation, differentiation, and activation of MCs 32,33 . Some transcription factors such as Crem, fosB, and Nr4a3 are known to be involved in FcεR‐mediated immune responses of MCs 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are similarly found in GATA2 deleted-DNA domain in mice BMMCs [ 51 ]. GATA2 also affects Mcpt1 and Mcpt2 gene expression, which are specific proteases in mucosal mouse mast cells [ 54 ].…”
Section: Transcriptions Factors Involved In Anaphylaxismentioning
confidence: 99%
“…GATA1 and GATA2 regulate tryptases (including mTMT, mMCP6, and mMCP7). Furthermore, GATA2 regulates histamine and proteases (Cpa3, Mcpt4, Mcpt8, Cma1) synthesis [ 27 , 54 ]. GATA3 defines a Tfh13 population involved in anaphylactic IgE production [ 59 ].…”
Section: Figurementioning
confidence: 99%